A new freshwater goby of Rhinogobius lingtongyanensis (Teleostei, Gobiidae) from the Dongshi river basin, Fujian Province, southeastern China - Chen, I-Shiung; Wang, Shen-Chih; Chen, Kwang-Yiao; Shao, Kwang-Tsao (Zootaxa, 2022)
A new species of freshwater gobiid fish of genus Rhinogobius Gill, 1859, were collected from the upper tributary of Dongshi river basin of Janchou City in southern region of Fujian Province, China. Rhinogobius lingtongyanensis n. sp. can be well distinguished from other congeners by the following features: (1) fins: second dorsal fin rays I/8; anal fin rays I/7; pectoral fin rays modally 16; (2) squamation: longitudinal scale series 25-27 (modally 26); predorsal scales 3-6 (modally 5-6); (3) vertebral count 26; and (4) specific colouration in male: lateral body with 6-7 major patches of irregularly grayish to brownish black marks; cheek blackish brown with four oblique grayish black stripes; branchiostegal membrane grayish blue without any light spots; first dorsal fin broad grayish brown band in middle, outer margin pinkish orange; pectoral fin base with longitudinal deep brown bar in upper region; and caudal fin gray with four vertical rows of brown spots, its base with a short brownish black bar. It belongs to the non-diadromous, fluvial hill-stream species. A diagnostic key to all valid species from Fujian Province, China is also provided in this paper.